Assessing the Production and Nutritive Value of Warm‐Season Legumes in Oklahoma and Texas. Issue 1 (1st December 2013) - Butler, Twain J.; Interrante, Sindy M.; Foster, Jamie L.
Abstract : Inclusion of warm‐season forage legumes in livestock grazing systems may increase forage quantity by maintaining the grazing season during dry periods and enhancing nutritive value. Two field experiments were conducted to evaluate forage yield and nutritive value of several warm‐season legumes across different environments and soil pH levels in Oklahoma and Texas. The superior forage yield and nutritive value of Lablab purpureus (L.) Sweet 'Rongia' lablab and Vigna unguiculata (L.) Walp. 'Iron & Clay' cowpea, Glycine max (L.) Merr. 'Big Fellow', 'Derry', 'Hutcheson', 'Laredo', 'Large Lad', 'Ozark', and 'Tyrone' soybeans, and Glycine soja Siebold & Zucc. x max 'Whitetail Thicket' hybrid soybean in both near‐average and below‐average rainfall years indicate their potential for livestock production. However, further research on best management strategies, animal performance, and economics of these cultivars is warranted before being included in production systems.